Changing Pattern of Agricultural Mechanization in Nalanda District of Bihar - Sagar, Sandip (Journal of Advanced Research in English & Education, 2021)
In agricultural production, farm mechanisation is a very necessary input. The number of tractors has increased rapidly, and in recent years, the population of draught animals has decreased in Bihar. A study was conducted in Nalanda District of Bihar, to classify the trend of tractor use and their economics. Mechanization is one of the most striking and pervasive phenomena of our times. Unfortunately, its study has been neglected by the social sciences, which have not sufficiently recognized that while technology itself belongs to the field of the natural sciences, its far-reaching effects on social life make it a vital subject for study by the social sciences. Insufficient and high variable precipitation and low fertility are major constraints to agricultural productivity. This brings the role of irrigation facilities and use of fertilizers. India is witnessing growth in irrigation facilities. Wells, canals and dams are constructed to cater needs of farmers. However, there is a lot to be achived in this regard. Applaying fertlizes are increasing day by day. It increases production as well as productivity of the field. At the same time, there is rampat mechanization of agriculture. Thus, it reduces human efforts and increases production of the field. How to cite this article:  Sagar S. Changing Pattern of Agricultural Mechanization in Nalanda District of Bihar. J Adv Res Eng & Edu 2020; 5(2): 1-4. DOI: https://doi.org/10.24321/2456.4370.202004